1998
DOI: 10.1046/j.1365-2915.1998.00082.x
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito carboxylesterases: a review of the molecular biology and biochemistry of a major insecticide resistance mechanism

Abstract: The major mechanism of organophosphorus insecticide resistance in Culex mosquitoes involves the elevation of one or more esterases. The general mechanism underlying this resistance is the amplification of the structural genes. This review covers the classification of the mosquito esterases in the context of classical esterase nomenclature. The function of the amplified esterases and the structure of the amplified DNA on which they occur are also described. Implications of information on the esterase amplicons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
176
1
6

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(198 citation statements)
references
References 79 publications
11
176
1
6
Order By: Relevance
“…The other esetrases were detected almost in all collected samples with frequency which vaired between 0.03 and 0.48. Esterases play an important role in the resistance of several insects in the world [25][26][27][28][29][30][31]. Our results confirms the previous results of Ben Cheikh et al [28] which reported the existence of a correlation between the frequency of individuals possessing the Ace-1R allele and those overproduced esterases A and B among the Tunisian populations of Culex pipiens.…”
Section: Hereditary Geneticssupporting
confidence: 82%
“…The other esetrases were detected almost in all collected samples with frequency which vaired between 0.03 and 0.48. Esterases play an important role in the resistance of several insects in the world [25][26][27][28][29][30][31]. Our results confirms the previous results of Ben Cheikh et al [28] which reported the existence of a correlation between the frequency of individuals possessing the Ace-1R allele and those overproduced esterases A and B among the Tunisian populations of Culex pipiens.…”
Section: Hereditary Geneticssupporting
confidence: 82%
“…COE genes, which play an important role in the metabolism of a wide range of xenobiotics associated with plants and insecticides 22,[28][29][30] , also showed large expansions of lepidopteran and α classes ( Table 1, Supplementary Fig. 6a and Supplementary Table 15).…”
Section: Nature Ecology and Evolutionmentioning
confidence: 99%
“…The most prevalent amplified esterase genes are estα2" and estβ2", which occur worldwide [1,14,15]. Some insects have variants of estβ1 (alleles of estβ2") that might or might not have a co-amplified estα3 [16].…”
Section: Introductionmentioning
confidence: 99%